The reality of psychological stress among the wives of the schizophrenics who used to visit Al-Sourani governmental clinic in the Gaza Strip: Case Study - Ghourab, Asmaa Abdelqader (Journal of Educational and Psychological Sciences, 2020)
This study aims at identifying stress represented in psychological, social, family, and economic pressure of the schizophrenics’ wives who used to visit Alsourani Governmental Clinic. In order to achieve the goal of the study, the researcher used the descriptive and the quantitative approaches, whereas the questionnaire consisted of 55 items as a measurement of the stress which was applied on a purposive sample consisted of 31 wives of the schizophrenia patients form Alsourani psychiatric clinic in Gaza. In addition, the researcher conducted 7 interviews with 4 wives of the schizophrenia patients and with 3 field psychiatric clinical consultants. The overall score of the stress scale was averaged 2.45 out of 3 which indicates that the stress degree is high. Concerning the level of the dimensions, the fourth dimension represented in the economic pressures ranked first with an average 2.68 out of 3, While the third dimension regarding the family pressures averaged 2.50 out of 3, whereas both are with a high degree. The first dimension represented in the psychological stress was in the third rank with an average of 2.48 out of 3. While the second dimension concerning the social pressures averaged 2.24 out of 3, whereas both are with a high degree. Based on the results, the researcher recommended that it is necessary to rehabilitate the schizophrenic in the governmental and non-governmental organizations according to the tendency and abilities and providing them with jobs. In addition, it is necessary to give a hand to the wives of the schizophrenics through economic empowerment.